Pengaruh Motivasi Kerja Dan Kepuasan Kerja Terhadap Komitmen Organisasi Pada Hotel Grand Fatma Tenggarong - Sari, Nilam Anggar; Isma, Siti Zulfa (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2018)
Abstract :The purpose of this study is to analyze the effect of work motivation and job satisfaction on organizational commitment. Objects in this study are work motivation, job satisfaction and organizational commitment. The research was conducted at Grand Fatma Hotel Tengarong. The population in this research is 48 employees with sampling using census approach. The data were collected by observation, interview and questionnaire. Analyzer used is multiple linear regression. The result of this research is, partially, work motivation and job satisfaction has positive and significant effect to organizational commitment. The analysis using the coefficient of determination work motivation and job satisfaction simultaneously variable influence on organizational commitment by 75.2 % while the remaining 24.8 % is the influence of other variables not examined in this study such as compensation and work competition. Meanwhile, the variable which has dominant influence to the organizational commitment is job satisfaction because its partial coefficient determination is the biggest when it is compared to other variables.Â Keywords: work motivation, job satisfaction, organizational commitment